Calculate: (9x)/(15)-(12x)/(15)=(15)/(15)+(3)/(15)-(5)/(15)

Expression: $\frac{ 9x }{ 15 }-\frac{ 12x }{ 15 }=\frac{ 15 }{ 15 }+\frac{ 3 }{ 15 }-\frac{ 5 }{ 15 }$

Any expression divided by itself equals $1$

$\frac{ 9x }{ 15 }-\frac{ 12x }{ 15 }=1+\frac{ 3 }{ 15 }-\frac{ 5 }{ 15 }$

Calculate the sum or difference

$\frac{ 9x }{ 15 }-\frac{ 12x }{ 15 }=\frac{ 13 }{ 15 }$

Multiply both sides of the equation by $15$

$9x-12x=13$

Collect like terms

$-3x=13$

Divide both sides of the equation by $-3$

$\begin{align*}&x=-\frac{ 13 }{ 3 } \\&\begin{array} { l }x=-4 \frac{ 1 }{ 3 },& x=-4.\overset{ \cdot }{ 3 } \end{array}\end{align*}$